Participatory conservation approaches for upgrading historic areas in Cairo:a case study of Al-Moez street and Al-Khalifa district - Abdelkader, Omar Ahmed (AUC Knowledge Fountain, 2020)
Historic Cairo is known for its rich heritage. The area suffered from severe deterioration in the recent few years due to several reasons, like the rise of underground water level and the 1992 earthquake. The historic city started gaining attention back in 1979 when it was listed as a World Heritage Site. Accordingly, different conservation projects were implemented in the city. The majority of these projects focused on tourism enhancement while neglecting the local community. Thus, the quality of life in these areas declined significantly and a lot of residents left for new neighborhoods. There are several international approaches for heritage conservations; most of them focus on integrating the local community within the process of conservation. The research examined the current heritage management system in Egypt and identified its weaknesses like the duplication of roles among different entities and lack of community mediators. The research also examined two conservation cases: Al-Moez street regeneration project and Athar Lina initiative in Al-Khalifa district. Each project had its own philosophy. Al-Moez street initially was meant to follow a culture tourism theoretical approach which focused on enhancing tourism. However, the implementation of the project was not based on any theoretical approaches; it focused on the physical sustainability of the area while ignoring the social and economic aspects. The end result of the process was different from the original intentions. The street lost a big part of its character and turned into a dead museum. The physical sustainability was not even maintained as the shape of the place changed significantly just a few years after the implementation of the project. On the other hand, Athar Lina followed a living heritage approach which focused on local community empowerment as a key for conservation. The initiative aimed at the collective transformation of context through a variety of activities that triggered socio-economic development and heritage education. The result behind the whole process was acceptable since the residents expressed their satisfaction towards the transformation. It was concluded that the living heritage approach is a suitable option for the context of Historic Cairo as it focuses on all dimensions of sustainability.